(untitled) - Stone, Robert J. (Boston, 2006)
This unique atlas is a study guide to the anatomy and actions of human skeletal muscles. It is designed for use by students of anatomy and physiology, physical therapy, chiropractic, medicine, nursing, physical education, and other health-related fields. This concise, compact reference shows the origin, insertion, action, and innervation of all human skeletal muscles. Students and instructors appreciate this atlas for the simplicity of the line art which helps students learn the main structures without overwhelming them with detail.
Keywords: Striated muscle,Cơ vân